The selective antagonism of P2X7 and P2Y1 receptors prevents synaptic failure and affects cell proliferation induced by oxygen and glucose deprivation in rat dentate gyrus. - Giovanna Maraula; Daniele Lana; Elisabetta Coppi; Francesca Gentile; Tommaso Mello; Alessia Melani; Andrea Galli; Maria Grazia Giovannini; Felicita Pedata; Anna Maria Pugliese (PLoS ONE)
Purinergic P2X and P2Y receptors are broadly expressed on both neurons and glial cells in the central nervous system (CNS), including dentate gyrus (DG). The aim of this research was to determine the synaptic and proliferative response of the DG to severe oxygen and glucose deprivation (OGD) in acute rat hippocampal slices and to investigate the contribution of P2X7 and P2Y1 receptor antagonism to recovery of synaptic activity after OGD. Extracellular field excitatory post-synaptic potentials (fEPSPs) in granule cells of the DG were recorded from rat hippocampal slices. Nine-min OGD elicited an irreversible loss of fEPSP and was invariably followed by the appearance of anoxic depolarization (AD). Application of MRS2179 (selective antagonist of P2Y1 receptor) and BBG (selective antagonist of P2X7 receptor), before and during OGD, prevented AD appearance and allowed a significant recovery of neurotransmission after 9-min OGD. The effects of 9-min OGD on proliferation and maturation of cells localized in the subgranular zone (SGZ) of slices prepared from rats treated with 5-Bromo-2'-deoxyuridine (BrdU) were investigated. Slices were further incubated with an immature neuron marker, doublecortin (DCX). The number of BrdU+ cells in the SGZ was significantly decreased 6 hours after OGD. This effect was antagonized by BBG, but not by MRS2179. Twenty-four hours after 9-min OGD, the number of BrdU+ cells returned to control values and a significant increase of DCX immunofluorescence was observed. This phenomenon was still evident when BBG, but not MRS2179, was applied during OGD. Furthermore, the P2Y1 antagonist reduced the number of BrdU+ cells at this time. The data demonstrate that P2X7 and P2Y1 activation contributes to early damage induced by OGD in the DG. At later stages after the insult, P2Y1 receptors might play an additional and different role in promoting cell proliferation and maturation in the DG.